PRODUCTIVE PERFORMANCE AND CHEMICAL COMPOSITION OF GROWERS PIG MEAT FED WITH Terminalia mantaly LEAVES - AKPORHUARHO, P. O.; OWEDE, C. D. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2021)
This investigation was conducted at the piggery breeding unit of the faculty of agriculture, Delta State University, Asaba, for 56 days to assess the effect of Terminalia mantaly leave inclusion in pig feed and its effect on carcass and meat quality. A total number of unsex forty weaner pigs were used for the study. Animals were put into four treatments groups with two replicates each (10 pigs per replication) using completely randomized design. The control group was fed without Terminalia mantaly leaves inclusion. Research work revealed significantly (P<0.05) different in all parameters, except the Moisture content of the chemical composition that showed no significant (P>0.05) different. Treatment 1 that received concentrate diet had a significant (P<0.05) increase in their Body length, Girth Circumference and Length of Ham although not significantly different from treatment 2 when compared with treatment 3 and 4 carcasses. Treatment 4 carcass exerted a significantly (P<0.05) higher increase in Breath of Ham cults, as compared with Treatment 1 and 2, the list was Treatment 3. Results obtained from the chemical composition of carcass cut of the weaner pigs fed processed Terminalia mantaly leaves showed that Treatment 1 had significant (P>0.05) higher content of all the parameters evaluated although not significantly (P>0.05) different from Treatment 2, Treatment 4 value of Ether extract and Ash are not statistically different from Treatment 1 and 2. By this feeding trials, Terminalia mantaly leaves fed to the pigs had no effect on their meat quality and quantity of the pigs and Terminalia mantaly leaves could be used as an alternative feed stuff for feeding pigs in order to attain cheaper meat that is rich in nutrient to Nigerians.